Mucinous cystadenoma of pancreas with honeycombing appearance: Radiological-Pathological correlation - Jefferson, Beno; Venkatraman, Indiran; Kumar, R Vinoth; Ponnuswamy, Karkuzhali; Anbukkarasi; Maduraimuthu, Prabakaran (Indian Journal of Radiology and Imaging, 2018)
Most mucinous cystadenomas of pancreas are solitary and multilocular with a few large compartments. Serous cystadenomas usually have a polycystic or microcystic (honeycomb) pattern consisting of collection of cysts (usually >6) that range from few millimetres up to 2 cm in size. Here we present a case of mucinous cystadenoma of pancreas showing an unusual appearance of honeycombing (which has not been described so far) using imaging studies such as endoscopic ultrasound and computed tomography with histopathological confirmation of the diagnosis.
Keywords: Cystic; honeycombing; Mucinous; pancreatic; tumors